2018
DOI: 10.1021/acs.cgd.8b00684
|View full text |Cite
|
Sign up to set email alerts
|

Stable Cocrystals and Salts of the Antineoplastic Drug Apatinib with Improved Solubility in Aqueous Solution

Abstract: Apatinib (APA) belongs to the targeted antineoplastic family of drugs by inhibiting the vascular endothelial cell growth factor receptor (VEGFR-2) of tyrosine kinase. APA encounters poor aqueous solubility problems, and its therapeutic dosage form, apatinib mesylate (ATM), is unstable and dissociates completely to APA in aqueous solution. Here, we synthesized and evaluated three new cocrystals of APA with adipic acid (APA + ADA), sebacic acid (APA + SEA), and D/L-mandelic acid (APA + D/L-MA), and four new salt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 58 publications
(101 reference statements)
1
27
0
1
Order By: Relevance
“…Top 10 interaction partners for APA were recommended (Table 4), in which fumaric acid, succinic acid, adipic acid, oxalic acid, benzoic acid, malonic acid, glutaric acid, 4-aminobenzoic acid, and 4-hydroxybenzoic acid have been found to form cocrystals with APA in previous studies. 28,42 In this study, paradioxybenzene (PDB) was subject to experimental screening and found to form a new cocrystal with APA. This new APA-PDB cocrystal was analyzed by powder X-ray diffraction (PXRD) to distinguish it from the parent phases (see Figure 6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Top 10 interaction partners for APA were recommended (Table 4), in which fumaric acid, succinic acid, adipic acid, oxalic acid, benzoic acid, malonic acid, glutaric acid, 4-aminobenzoic acid, and 4-hydroxybenzoic acid have been found to form cocrystals with APA in previous studies. 28,42 In this study, paradioxybenzene (PDB) was subject to experimental screening and found to form a new cocrystal with APA. This new APA-PDB cocrystal was analyzed by powder X-ray diffraction (PXRD) to distinguish it from the parent phases (see Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…The cocrystal screening of apatinib (APA), which is a clinical drug for advanced gastric cancer, was conducted by the guidance of SMINBR. Although APA has been reported to form pharmaceutical cocrystals in recent publications, , these cocrystals do not exist in the constructed molecular-interaction network, because the cocrystal data used for network construction were retrieved before 2016. Therefore, APA can be viewed as an NCE and used to evaluate the capability of SMINBR to guide experimental cocrystal screening for new synthetic compounds.…”
Section: Resultsmentioning
confidence: 99%
“…The market value of a drug can be drastically reduced due to its poor physicochemical properties, which in turn can cause the demand to replace it. This is the major reason why there is an increased interest in the physicochemical properties upgradation methods such as salt formation [3]. Pharmaceutical salts are ionizable drugs that have been combined with a counter-ion to form a neutral compound.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the research on cocrystals has become increasingly erce, especially in the pharmaceutical industry. [1][2][3][4][5][6][7][8][9][10] In the pharmaceutical eld, a drug cocrystal is a crystalline solid containing at least one active pharmaceutical ingredient (API) and one or more cocrystal coformers (CCFs). These substances exist in one crystal lattice, and the molecules connected through non-ionic way interacting.…”
Section: Introductionmentioning
confidence: 99%